Registration and local production of essential medicines in Uganda - Petra Brhlikova; Karen Maigetter; Jude Murison; Amon G. Agaba; Jonans Tusiimire; Allyson M. Pollock (Taylor & Francis Group, 2020)
Background Universal access to high quality essential medicines is critical to sustainable development (SDG 3.8). However low- and middle-income countries struggle to ensure access to all medicines on their national essential medicines lists (EML). Market registration is the first step in determining both access and availability yet the extent to which essential medicines are registered for use at country level is not known. Companies apply for a marketing authorisation, however low price or lack of a market is a disincentive. Local production has been promoted to ensure availability of essential medicines but research in this area is also limited. Methods The study took place between 2011 and 2015. We systematically examined the registration status of medicines and vaccines listed in the Ugandan 2012 EML and conducted 20 interviews with regulators, ministry of health representatives, donors, and pharmaceutical producers and analysed quality assurance issues affecting registration, procurement, and local production of medicines in Uganda. In 2017 we conducted a further three interviews to clarify issues around non-registration of essential medicines highlighted by our analysis. Results Of the 566 essential medicines and vaccines nearly half (49%; 275/566) had no registered product in 2012. Of the 3130 registered products, just over a quarter (28%; 880/3130) were listed on the EML. Six local producers had registered 138 products of which 40 corresponded to 32 unique essential medicines. Interviews highlighted alternative routes to availability other than registration. Local producers faced considerable barriers to achieving international quality standards required for international procurement of medicines for the domestic market. Conclusions Monitoring and audit of the registration of essential and non-essential medicines should be a priority nationally and, regionally through harmonisation of registration requirements in the East African Community. National and regional manufacturing plans should consider local production of unregistered essential medicines.